DETERMINATION OF STUDENTS ' KNOWLEDGE USING A NON-STANDARD TEST WHEN TEACHING THE TOPIC OF THE CHEMICAL BASIS OF LIFE PROCESSES - Akhmadzhonova M.S, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article is devoted to the issues of using non-standard tests in strengthening the cognitive activity of students when teaching the topic “chemical foundations of life processes” in biology.